Exploring the relations between selected emotional intelligence scale among three different combat sports: a correlation analysis - Rani, P.; Lodhi, A.; Vijay, R.; Kumar, S.; Singh, R. (American Journal of Sports Science, 2023)
Background: The research scholar selected this present research study to explore the relationship between selected emotional intelligence variables among sportspersons of selected three different games and sports. Objective; To determine the coefficient of correlation between selected Emotional intelligence variables among boxing, wrestling, and taekwondo players Measure; According to the supervisor's and research experts' guidance, the research scholar used the emotional intelligence scale (EIS; Anukool Hyde et, al. 1971) based on 5 items Likert scale. The above-mentioned Questionnaire had high reliability and acceptable construct validity (r =.0.88, V = 0.93). Therefore, the scales were found to have adequate properties and to be applicable in research and practice. Hypothesis; It was hypothesized that a statistically significant positive strong correlation would be found between selected Emotional intelligence variables among selected sportspersons. Statistics; To calculate the mean and correlation the research scholar used descriptive statistics (M, SD), and Pearson product-moment correlation in the IBM® SPSS Statistics analysis package. Results: In the present research study, revealed that there was a statistically significant coefficient correlation found between selected Emotional intelligence variables among boxing, wrestling, and taekwondo players, Boxing (M = 135.66, ± SD = 54.83), Wrestling (M = 123.11, ± SD = 50.21), and Taekwondo (M = 144.66, ± SD = 60.72), and Pearson product-moment correlation was found between cumulative score among boxing and wrestling (r = 986**, p = 0.01), boxing and taekwondo (r = 994**, p = 0.01), and the wrestling and taekwondo (r = 989**, p = 0.01), The result indicated that a statistically significant very positive correlation was found between the selected psychological variables among boxing, wrestling and taekwondo players at significance level 0.01.